2019
DOI: 10.1002/srin.201900470
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Gap Between Copper Mold and Solidified Shell on the Fluid Flow in the Continuous Casting Strand with Mold Electromagnetic Stirring

Abstract: Considering the gap between the copper mold and the solidified shell (mold-bloom gap), the electromagnetic field, fluid flow, solidification, removal of inclusions, and slag entrainment in the bloom continuous casting process with mold electromagnetic stirring (M-EMS) are numerically investigated. As the mold-bloom gap is considered, the electromagnetic force increases with the distance from the meniscus and reaches a maximum value near the stirrer center. With the distance further increasing, the electromagne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…The measured position of 20 mm beneath the loose-side surface almost corresponded to shell thickness in the stirrer center during the CC process. [6] The deflection angles obtained from the position of 20 mm beneath the loose-side surface were 25.0 , 26.85 , 29.44 , and 32.49 in the current intensities of M-EMS 100, 200, 300, and 390 A, respectively. With the increase in the current intensity of M-EMS, the tangential velocity near the solidification front increased, and the deflection angle increased.…”
Section: The Deflection Angle Of Columnar Dendrites On the Cross Section Of 20crmnti Bloom Under Different Current Intensities Ofmentioning
confidence: 89%
See 2 more Smart Citations
“…The measured position of 20 mm beneath the loose-side surface almost corresponded to shell thickness in the stirrer center during the CC process. [6] The deflection angles obtained from the position of 20 mm beneath the loose-side surface were 25.0 , 26.85 , 29.44 , and 32.49 in the current intensities of M-EMS 100, 200, 300, and 390 A, respectively. With the increase in the current intensity of M-EMS, the tangential velocity near the solidification front increased, and the deflection angle increased.…”
Section: The Deflection Angle Of Columnar Dendrites On the Cross Section Of 20crmnti Bloom Under Different Current Intensities Ofmentioning
confidence: 89%
“…The distribution of electromagnetic force was circumferential and maximum values were located near the solidification front. The industrial trials revealed that the optimum parameters of F-EMS were 380 A, 6 Hz, and the central segregation index could reach 1.04. Ayata et al [1] investigated the effect of combination stirring on the improvement of macrosegregation by industrial trials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transient external magnetic field was generated from the alternating current. The magnetic flux density and the current distribution were solved in a transient solver [39,40]. The following three equations were computed in the solver:…”
Section: Electromagnetic Stirring Forcementioning
confidence: 99%
“…The radiation boundary condition was set on the top of the ingot; the heat flux was calculated by Equation ( 8). [23,24]…”
Section: Boundary Conditionsmentioning
confidence: 99%